MORPHOLOGICAL JUSTIFICATION OF THE STEPWISE DOSED BALLOON ANGIOPLASTY APPLICATION COMPARED TO STANDARD METHODS IN PATIENTS WITH DIABETIC FOOT - Puzyrov, G.S.; Lyakhovskyi, V.I.; Shepitko, V.I.; Sydorenko, A.V. (World of Medicine and Biology, 2020)
The main reason for the development of lower extremities gangrene in diabetes mellitus is impairment of their blood supply. In recent decades, endovascular surgical treatment has played a significant role in restoring blood supply. However, the issues of complications that arise after such interventions, the reasons for their occurrence, what morphological changes occur in the atherosclerotic artery wall during their implementation remain understudied. Therefore, experimental research to study the local changes that occur in the arteries of the lower extremities during balloon angioplasty, especially in patients with ischemic diabetic foot, is an urgent problem of modern interventional surgery. The purpose of the study was to provide a morphological justification for the use of stepwise dosed balloon angioplasty using balloons of different diameters and lengths compared to standard methods in patients with ischemic form of diabetic foot syndrome. An experimental study was performed on 20 lower limbs that were amputated at the hip level for foot gangrene in patients with ischemic form of diabetic foot syndrome. The first group included 5 (25.0%) lower extremities, in which immediately after the surgery, sections of the tibial arteries with stenosis of more than 75% were sampled. Group II included 5 (25.0%) amputated lower extremities, which immediately after the surgery were performed a typical balloon angioplasty. Group III included 10 (50%) amputated lower extremities, in which the method of stepwise dosed balloon angioplasty was tested. According to the results of experimental studies, it was found that mainly when performing staged dosed angioplasty according to the proposed method, the inner elastic membrane of the artery was clearly pronounced, had insignificant areas of fragmentation. At the same time, the outer elastic membrane was quite well pronounced throughout the whole length, had insignificant areas of fragmentation and they were much less in number than in those cases when angioplasty was performed according to standard methods. Moreover, in the outer membrane, where vasa vasorum and vascular nerves were located, they remained almost unchanged. Reducing the number and sizes of arterial membranes’ dissection, their fragmentation when performing staged dosed balloon angioplasty by the proposed method using balloons of different diameters and lengths permits to recommend it in practice to reduce the incidence of thrombotic complications in the early postoperative period.